2020
DOI: 10.1007/s00441-020-03247-0
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of R-GSIK scaffold with mesenchymal stem cells improves neuroinflammation in a traumatic brain injury model

Abstract: Neural tissue engineering has been introduced as a novel therapeutic strategy for traumatic brain injury (TBI). Transplantation of mesenchymal stem cells (MSCs) has been demonstrated to improve functional outcome of brain injury, and RADA4GGSIKVAV (R-GSIK), a self-assembling nano-peptide scaffold, has been suggested to promote the behavior of stem cells. This study was designed to determine the ability of the R-GSIK scaffold in supporting the effects of MSCs on motor function activity and inflammatory response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Increased survival and migration of engrafted hNS/PCs in PM could be due to significantly improved biocompatibility and integration with the host tissue, which promotes the regeneration of damaged spinal cord tissue [24,39]. Hydrogel scaffolds play a shielding role against the host immune system and exhibit anti-gliosis and anti-inflammatory properties when fused with host tissue [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Increased survival and migration of engrafted hNS/PCs in PM could be due to significantly improved biocompatibility and integration with the host tissue, which promotes the regeneration of damaged spinal cord tissue [24,39]. Hydrogel scaffolds play a shielding role against the host immune system and exhibit anti-gliosis and anti-inflammatory properties when fused with host tissue [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral scoring found that functionalized scaffolds loaded with MSCs enhanced TBI recovery in rats and significantly reduced the numbers of astrocytes and microglia, which release inflammation-related factors after TBI (Figure 3C). Subsequent Western blot analysis also found a reduction in related pro-inflammatory factors, confirming that the combination could improve stem cell survival after transplantation by inhibiting the inflammatory response [53].…”
Section: Motifs From the Extracellular Matrix (Ecm)mentioning
confidence: 72%
“…Even though a variety of bioengineering approaches aiming to facilitate and optimize MSC treatments have emerged throughout the decade, ensuring efficient engraftment and survival of implanted MSCs remains a challenge (Hmadcha et al, 2020b). To address this obstacle, researchers are using biomaterials as scaffolds designed to improve the retention of transplanted cells (Zeng et al, 2015b;Zhang et al, 2018b;Ryu et al, 2019c;Yan et al, 2019;Deng et al, 2020;Sahab Negah et al, 2020;Ma et al, 2021b;Restan Perez et al, 2021). Efforts are being made to produce ideal biodegradable and biocompatible scaffolds based on both synthetic and natural polymers that mirror the biological and mechanical properties of the target tissue (Doblado et al, 2021).…”
Section: Novel Biomaterialsmentioning
confidence: 99%
“…A study by Negah et al utilized an experimental TBI model in rats to assess whether RADA4GGSIKVAV (R-GSIK), a selfassembling nano-peptide scaffold, brings quantifiable benefits in the form of functional improvement and decrease in neuroinflammation (Sahab Negah et al, 2020). Interestingly, a significant functional recovery was observed in rats that received MSCs with R-GSIK scaffolding, as opposed to those in the control group.…”
Section: Novel Biomaterialsmentioning
confidence: 99%